2017
DOI: 10.3400/avd.cr.16-00045
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair for Kommerell’s Diverticulum and Right-Sided Aortic Arch

Abstract: A 74-year-old man with hoarseness was diagnosed with a right-sided aortic arch and Kommerell’s diverticulum by computed tomography (CT). The diverticulum had a maximum diameter of 33 mm, and surgical intervention was chosen because of the possibility of rupture. A right common carotid to right subclavian artery bypass was constructed, stent-graft was placed after the branching of the right common carotid artery, and coil embolization of the diverticulum was performed via left brachial artery. No leaks were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…In recent years, there have been reports of employing TEVAR to manage KDs associated with a right aortic arch. Kazuno et al reported a successful TEVAR with positive results in a KD patient, who had similar anatomy to the patient in the present case [Kazuno 2017].…”
Section: Discussionsupporting
confidence: 63%
“…In recent years, there have been reports of employing TEVAR to manage KDs associated with a right aortic arch. Kazuno et al reported a successful TEVAR with positive results in a KD patient, who had similar anatomy to the patient in the present case [Kazuno 2017].…”
Section: Discussionsupporting
confidence: 63%
“…Kommerell diverticulum has been repaired successfully endovascularly, which is often the repair strategy. 7 , 8 In one review of patients with a right-sided aortic arch and Kommerell diverticulum, 6% of the patients presented with rupture and 47% with dissection. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Although endovascular stenting with cervical debranching has been described successfully, we did not believe this would be safely feasible, given the proximity of the pseudoaneurysm to the left carotid artery with an inadequate landing zone. 7 , 8 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no matter which devices are used to treat ALSA, there remain 2 basic techniques: proximal exclusion with/without blood flow reconstruction. Percutaneous coil embolization of the proximal segment of the ALSA was performed by coils or plugs after deployment of the device in some cases [ 16 , 21 ]. However, some researchers were concerned that intentional coverage of the ALSA during TEVAR would increase the risk of upper-extremity subclavian steal syndrome, or possibly of spinal cord ischemia.…”
Section: Discussionmentioning
confidence: 99%